Growth of Morphology Seedling Papaya (Carica papaya L.) To Lengthy Variation Soaking Temperature and Receptacle Pre- Germination - Assauwab, Muhammad Husaini (Jurnal Online Pertanian Tropik, 2021)
Papaya is one of the leading tropical fruit that is very potential to be developed in Indonesia. Various treatments to solve dormancy of papaya seeds have been done, from sarcotesta disposal and administration, temperature treatment has shown varying results, so there is still no definite information about the way or treatment which is most appropriate for breaking the dormancy of papaya seeds. Therefore, the researchers wanted to do research on the Development of Morphology of Papaya Seedlings (Carica papaya L.) With Various Old Immersion Temperature and Pre-Germinary receptacle. Parameters seen are among others height of the plant and the length of the root. From this treatment, it is clear that the effect of the interaction of various immersion temperatures with pre-sprouted receptacle to Root Length Carica papaya L is significantly different.